Polymorphisms in thrombophilia and renin–angiotensin system pathways, preterm delivery, and evidence of placental hemorrhage - Gargano, Julia Warner (2009)
OBJECTIVE: To analyze functional polymorphisms in candidate genes (methylenetetrahydrofolate reductase (MTHFR)677C>T, MTHFR1298A>C, Factor 5 1691G>A (FVL), and angiotensinogen (AGT)-6G>A) in relation to a hypothesized placental hemorrhage pathway to preterm delivery (PTD). STUDY DESIGN: We assessed maternal genotypes, pregnancy outcomes, and placental pathology among 560 white and 399 black women recruited at midtrimester into a prospective cohort study (1998-2004). Odds of dominant genotypes were calculated for PTDs with (n=56) or without (n=177) evidence of placental hemorrhage (referent=term) using race-stratified polytomous logistic regression models. RESULTS: Among whites, FVL GA/AA and AGT(-6) GA/AA were both associated with hemorrhage-related PTDs (OR=4.8 [1.6, 14.2] and OR=3.8 [1.3, 10.5], respectively) but not other PTDs (ORs=1.2 and 0.9, respectively). FVL GA/AA was associated with PA (OR=5.8 [1.1, 30]) among white women. All results were null for MTHFR genotypes. CONCLUSION: FVL and AGT variant genotypes were specifically associated with hemorrhage-related PTDs.